Back protection of canvas paintings - Tim Padfield; Nicolas Padfield; Daniel Sang-Hoon Lee; Anne Thøgersen; Astrid Valbjørn Nielsen; Cecil Krarup Andersen; Mikkel Scharff (Heritage Science, 2020)
Abstract In this paper different scenarios for back protection of a canvas painting and their effect on the stability of the relative humidity behind the painting are tested. A painting on canvas, stretched on a wooden frame, was fitted with various styles of back protection and then exposed to a cycle of temperature variation at the back, with the front exposed to a constant room temperature. The painting was also exposed to a constant wall temperature and varying room temperature. The space between the canvas and the back board was fitted with temperature and relative humidity (RH) sensors. The sensors were used to provide the essential single-point data of temperature and RH at the given locations. For more comprehensive understanding of the rather confined space, further numerical simulation (computational fluid dynamics) was adopted as part of the investigation. The computational fluid dynamics was used to understand the natural convection within the microclimate through the depictions of temperature distribution, as well as the corresponding airflow. The unprotected painting suffered a large RH variation at its back, because of the varying canvas temperature interacting with the constant room air moisture content. Effective stabilisation of the RH behind the canvas against temperature variation was provided by a shiny aluminium alloy sheet sealed against the frame. The non-absorbent back board experienced a strong variation in RH, because of humidity buffering of the space by the painting canvas at a different temperature. Either a space or insulation between this back plate and the wall reduced the risk of condensation on the inner surface of the back plate. Insulation will however increase the risk of condensation on the wall surface behind the painting. An absorbent back board de-stabilised the RH at the painting canvas surface by providing a competing humidity buffer at a different temperature. To provide protection against moisture exchange with an unsuitable room RH, extra humidity buffer was placed 3 mm behind the painting canvas, kept close to the painting temperature by insulation between this buffer and the back board. This stabilised RH at the canvas surface but increased both the temperature and the RH variation at the back board and thus increased the risk of condensation on the inner surface of the back board. The RH and the temperature in the narrow spaces between the painting canvas and the wooden stretcher frame were always more nearly constant than in the open canvas area, which suggests an explanation for the widely observed better condition of the areas of canvas paintings which lie close over the support structure. Our conclusion is that a non-absorbent, impermeable back plate gives good RH stability against a changing temperature gradient between wall and canvas painting surface.